'The communities we live in': providing meaningful contexts for the application and generation of knowledge through service in Uganda. Issue 6 (2nd November 2018) - VanderDussen Toukan, Elena
Abstract: If service-learning is to fulfil its potential to contribute to meaningful social change, scholars and practitioners must consider how service might foster a dynamic relationship between knowledge, the learner and the community. This paper challenges modernist conceptions of knowledge as a 'commodity' that can be delivered and consumed, and instead identifies service to the community as a meaningful context for learners to interact with knowledge in a coherent framework for the explicit purpose of individual and social change. The Preparation for Social Action programme in Uganda is offered as an example in which relationships between knowledge, learners and the community can be examined. Findings from an analysis of curricular materials, participant observation and interview and focus-group data collected from its local instructors and administrators are discussed.